Psychological barriers to optimal insulin therapy: more concerns in adolescent females than males. Issue 1 (23rd June 2016) - Wisting, Line; Bang, Lasse; Skrivarhaug, Torild; Dahl-Jørgensen, Knut; Rø, Øyvind
Abstract : Objective: The aim of this study is to investigate psychological barriers (illness perceptions, insulin beliefs, and coping strategies) to optimal insulin therapy among adolescents with type 1 diabetes (T1D), with a specific focus on gender differences and mode of treatment (insulin pump vs pen). Methods: A total of 105 males and females (12–20 years) participated in this study. The Brief Illness Perception Questionnaire, the Beliefs about Medicines Questionnaire, and the Adolescent Coping Orientation for Problem Experiences were completed. Additionally, diabetes clinical data were collected by the Norwegian Childhood Diabetes Registry. Results: Females had significantly more negative illness perceptions than males on all dimensions (p<0.05), with moderate-to-large effect sizes. Regarding insulin beliefs, females scored significantly higher than males on insulin concern (p<0.001), indicating more concerns about insulin. There were no significant gender differences on perceptions of insulin necessity . Finally, females scored significantly higher on the coping strategies being social and solving family problems (p<0.01), indicating more positive coping among females than males for these subscales. In terms of treatment mode, the only statistically significant difference in the psychological aspects was for the illness perception treatment control, with patients using insulin pen reporting more negative perceptions on this dimension than patients using insulin pump. Conclusions: Addressing psychological aspects may be a clinically important supplement to standard somatic T1D care. The consistent finding of gender differences across the psychological measures implies that a tailored treatment approach for males and females with T1D may be warranted.